Analisis Lirik Lagu “Rakit” Karya Nadzira Shafa dengan Pendekatan Ekspresif - Sasi Aprilia (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2024)
This research analyzes the song "Rakit" by Nadzira Shafa using an expressive approach to explore the emotions and messages conveyed through the lyrics and music. Qualitative analysis shows that this song describes a deep emotional journey, involving sadness, longing, happiness, and the struggle to recover from loss. The representative, directive, expressive, declarative and commissive speech acts in the lyrics show emotional reality, an invitation to reassemble life, as well as a commitment to eternal memories and love. The song "Rakit" shows how music can be an effective communication medium for conveying personal experiences emotionally, while also providing room for interpretation for the listener.